Marginalization of Female Character under Patriarchal System in Craig Brewers’s Coming 2 America (2021) - Latifah Dwi Ariyani; Farid Khamidan (Metaphor, 2022)
This research is aimed to analyze gender roles reflected by the male and female characters in Craig Brewer’s Coming 2 America (2021) and the way male characters marginalize female characters in society under patriarchy system reflected in Coming 2 America (2021). The researcher applied descriptive qualitative method in analyzing Craig Brewer’s Coming 2 America (2021) as the objective of research. In analyzing the movie, the researcher used some theories such as gender study, gender Roles, and Walby’s patriarchy structures. The result of the study shows that male characters role are always in the higher position than female characters role in society that lead women to be marginalized ones and the way male characters marginalize female characters under patriarchy system that is found in five of six structures of patriarchy, namely, marginalization under patriarchy in household, marginalization under patriarchy in state, marginalization in form of male violence, marginalization in sexuality, and marginalization in culture.